What is Environmental Biotechnology? although widely applied, a clear definition of the term is still needed - Heaven, Sonia; Kusch-Brandt, Sigrid; Byfield, Louise; Bywater, Angela; Coulon, Frederic; Curtis, Thomas P.; Gutierrez, Tony; Higson, Adrian; Sadhukhan, Jhuma (MDPI, 2025)
The term Environmental Biotechnology is widely used, but lacks a universally accepted definition, with varying interpretations across disciplines and sectors leading to challenges in funding, policy formulation, and interdisciplinary collaboration. Through a literature review and engagement activities, this study examines existing definitions, identifies key areas of divergence, and explores pathways toward a more cohesive understanding. Findings reveal a spectrum of valid interpretations, often shaped by specific contexts, with researchers generally recognising a shared conceptual framework within their own subfields but encountering ambiguities across subject boundaries. Common points of difference include whether Environmental Biotechnology is restricted to microorganisms or encompasses other biological systems. Some understandings reflect sector-specific needs, contributing to fragmentation, though a broader approach could strengthen the field’s identity by providing a unifying framework, mapping overlaps with related fields such as Industrial Biotechnology. A working definition is proposed for Environmental Biotechnology as the use of biologically mediated systems for environmental protection and bioremediation, incorporating resource recovery and bioenergy production where these enhance system sustainability. Importantly, it was recognised that any definition must remain adaptable, reflecting the evolving nature of both the science and its applications.
Keywords: 41 Environmental Sciences; 15 Life on Land; 4104 Environmental management; 4105 Pollution and contamination; environmental biotechnology; environmental technology; definition; unifying framework; bioeconomy